BALKAN FEATURES OF AROMANIAN LANGUAGE - Poci, Spiridhulla (European Scientific Journal, ESJ, 2014)
This language, which belongs to the Latin population of Souhern Balkans, was neither ‘born’ anywhere, nor did it ’emerge’ as a new ethnic form. It is spoken by seperate groups of people in the South of Albania, Northern and Northwestern Greece, Former Yugoslav Republic of Macedonia and in Diaspora. This new pattern is a product of the Balkan Latin in the time of the Roman conquest,resulting from the interference of Latin with the native Balkan languages during the eighth century of the dominance of the Roman Empire. The conditions under which it was born, reciprocal impact of languages upon one another as well as the common historic destiny of the Balkan peoples, made it possible for this language to acquire several phonetic, morphological and syntactical features, already existing in the other Balkan languages.